ONLINE FOOD ORDER APPLICATION USING DJANGO (International Journal of Food and Nutritional Sciences, 2021)
With the growing popularity of food delivery, conventional phone order has become inconvenient for both customers and food delivery stores. People are concerned about how to make food delivery more timely and convenient. As a result, this research investigates and creates new takeaway apps that are simpler and more object-oriented than existing apps. Food delivery should be timely, convenient, and comprehensive. Many food delivery systems exist today, but their functions are not comprehensive, and some do not meet the requirements of timely delivery, friendliness, payment is too simple, the layout is too rigid, and information updates are not timely enough. An Online Food Ordering System that simplifies the food ordering procedure is proposed here. The proposed system updates the menu with all available options, easing the customer's job. Customers can place orders for multiple items and check order details before logging out. The customer receives an order confirmation. The order is queued, updated in the database, and returned in real-time. This technology enables personnel to go over orders in real-time and process them efficiently and with few errors.